Efektivitas Konseling Wellness Untuk Meningkatkan Psychological Well-Being Lansia - Lucia Hernawati; Praharesti Eriany (Universitas Katolik Soegijapranata, 2021)
The number of elderly (60-70 years old until death) in Indonesia increases from year to year. In the elderly phase, individuals begin to experience decreased physical function, cognition and relationships with friends. Thus, it is likely that the psychological well-being of the elderly will decline with declined life satisfaction and contribution to their community as the indicators. This community service activity aimed to help the elderly increase their happiness by providing wellness counseling services for 7 sessions (7 weeks). Through the wellness counseling services, the elderly were invited to evaluate their current lifestyle through self-discovery and to design and apply a new, holistic healthy lifestyle (physical-mental-social health) in order to live a life by maximizing self-actualization and contribution to the society. Henceforth the elderly will feel more satisfied with their lives and happier (the state of psychological well-being increases).